Percepção ambiental sobre aspectos de saneamento básico na cidade de Óbidos, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2018)
Basic sanitation is the set of infrastructure services and facilities that aim to improving the quality of life, environmental and public health conditions. O present study was carried out in the city of Óbidos, Pará to evaluate the the basic sanitation services, and the relationship that these services present with the health and well-being of the population and the environment. The methodology involved the application of a structured questionnaire to a sample of the residents of eight districts of the city; the same has issues regarding basic sanitation and issues related to the socioeconomic profile of residents. The period of data collection was from January to February 2018, 400 questionnaires were applied, 50 per neighborhood. The majority of respondents (54%) demonstrated that they do not know what basic sanitation is about because of the information on the subject. Most of the residents interviewed (89%) do not know what happens to the water before arriving at their homes and therefore carry out some kind of domestic treatment. Due to the concern with the quality of the water consumed and to avoid health problems people started to treat water at home with the aid of filters, purifiers, hypochlorite of sodium and by boiling. Regarding the fate of domestic sewage, 41% of residents responded that the sewage runs in the open. The public collection service of solid waste presents great satisfaction for occurring more than once per week. In relation to the drainage system, the residents believe that the solution to avoid flooding is investment in infrastructure and disposal of solid waste. Based on the study, it can be concluded that the majority of the interviewees is aware of the need for improvements related to the basic sanitation. It is therefore necessary to create conditions for services to be implemented correctly, as well as being accessible to the entire population to promote the development of the city and improve health and quality of life of people.
Keywords: Drenagem urbana; Educação ambiental; Esgotamento sanitário; Abastecimento de água; Limpeza urbana; CNPQ:: ENGENHARIAS